Functionalization Enhancement on Interfacial Properties Between Graphene and ZnO NW/Epoxy: A Molecular Dynamics Simulation Study. Issue 6 (7th March 2022) - Marashizadeh, Parisa; Abshirini, Mohammad; Saha, Mrinal; Huang, Liangliang; Liu, Yingtao
Abstract: This study presents the atomistic characterization of the fiber/matrix interfacial properties in the hybrid functionalized carbon fiber reinforced polymer composites. A molecular model is developed containing ZnO nanowire (NW) aligned vertically on functionalized graphene sheet (FGS) and embedded in the cross‐linked epoxy matrix. The molecular dynamics simulation technique is employed to evaluate the traction‐separation behavior of FGS in both opening and sliding modes. Three different chemical groups of carboxyl (COOH), carbonyl, and hydroxyl with multiple grafting densities are explored as functional groups. The results reveal that the interfacial strength and the cohesive energy are considerably enhanced in the functionalized model compared with the pristine structure. COOH has the most impact on the traction‐separation response with a 112% improvement of interfacial strength. The enhanced effect of functionalization is more intense in the shear separation than the normal one. However, comparing the graphene/ZnO NW with graphene/no ZnO NW structures show that adding ZnO NW can compensate for the slight effect of grafting in the normal direction. The results indicate that combining the growth of ZnO NW and functionalization enhances the interfacial strength up to two‐fold in the opening and up to eight‐fold in the sliding mode of carbon fiber composites. Abstract : The atomistic characterization of the fiber/matrix interfacial properties in the hybrid functionalized carbon fiber reinforced polymer composites shows that combining the growth of ZnO nanowires and functionalization improves the interfacial strength up to two‐fold in the opening and up to eight‐fold in the sliding mode. COOH functional group has the greatest impact on the traction‐separation behavior of the hybrid structure.